O DIÁLOGO COMO MÉTODO DE CONSTRUÇÃO DE DIREITOS: O MODELO DELIBERATIVO DE GESTÃO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
We intend to evaluate the effectiveness of the dialogue and of the democratic procedure as a method to formulate and enforcement rights. Such a proposal is criticized for its proceduralism, which ignores the substantive values and because of that do not offer sufficient protection to the political minorities. That proposal is also criticized for its choice of non-violence as an absolute value, which can endorse other violence consolidated by the status quo. Although reasonable, such criticisms do not put away the bet on dialogue as a temporary solution. But this bet should not be just rhetorical. Then, it is necessary to verify the effective methods of its implementation, which can be found, within the scope of government and public administration, in an expanded conception of social participation, which comes to the so-called deliberative model, below analyzed.